Faktor-faktor yang Mempengaruhi Kepuasan Pelanggan - Sari Sariatin; Christina Ekawati (SAFE-Network, 2023)
This study aims to analyze the influence of product quality, price, and service quality on customer satisfaction at PT Kanefusa Indonesia. The population of this research consists of PT Kanefusa Indonesia's customers, with a sample size of 75 individuals. The data analysis method used is Multiple Linear Regression. The results of the study indicate that the simultaneous hypothesis test shows that the variables of product quality, price, and service quality significantly affect customer satisfaction. Additionally, the partial hypothesis test demonstrates that each variable, namely product, price, and service quality, significantly influences customer satisfaction. This research provides valuable insights for PT Kanefusa Indonesia in understanding the factors that affect customer satisfaction. By paying attention to and improving product quality, offering competitive prices, and providing excellent service quality, PT Kanefusa Indonesia can better meet customer expectations and strengthen long-term relationships with customers. The findings of this study can also serve as a basis for designing more effective marketing and management strategies to enhance customer loyalty and achieve a competitive advantage in their industry.